Copper, ceruloplasmin, and long-term cardiovascular and total mortality (The Ludwigshafen Risk and Cardiovascular Health Study). (June 2014) - Grammer, T. B.; Kleber, M. E.; Silbernagel, G.; Pilz, S.; Scharnagl, H.; Lerchbaum, E.; Tomaschitz, A.; Koenig, W.; März, W.
Abstract Background. Copper and its main transport protein ceruloplasmin have been suggested to promote the development of atherosclerosis. Most of the data come from experimental and animal model studies. Copper and mortality have not been simultaneously evaluated in patients undergoing coronary angiography. Methods and results. We examined whether serum copper and ceruloplasmin concentrations are associated with angiographic coronary artery disease (CAD) and mortality from all causes and cardiovascular causes in 3253 participants of the Ludwigshafen Risk and Cardiovascular Health Study. Age and sex-adjusted hazard ratios (HR) for death from any cause were 2.23 (95% CI, 1.85–2.68) for copper and 2.63 (95% CI, 2.17–3.20) for ceruloplasmin when we compared the highest with the lowest quartiles. Corresponding hazard ratios (HR) for death from cardiovascular causes were 2.58 (95% CI, 2.05–3.25) and 3.02 (95% CI, 2.36–3.86), respectively. Further adjustments for various risk factors and clinical variables considerably attenuated these associations, which, however, were still statistically significant and the results remained consistent across subgroups. Conclusions. The elevated concentrations of both copper and ceruloplasmin are independently associated with increased risk of mortality from all causes and from cardiovascular causes.